Justification of Operation of Mercedes-Benz Buses After the Normative Life is Expired - Toxirjon-o‘g‘li, Karimov Islomjon; Jovliyev, Vasik Ulashevich; Inomjon-o‘g‘li, Otaqo‘ziyev Doniyor (European Journal of Life Safety and Stability (2660-9630), 2023)
This article is currently devoted to road transport physical wear and tear and a number of other reasons motor vehicles may become unusable for further operation. For passenger transport of the city of Tashkent, Mercedes Ben’s buses of modification O405, O345LF were purchased: 200 units in 2008, 200 units in 2009, 100 units in 2012. and 2013 - 100 units. The manufacturer recommends 1.0 million km for these buses before they are written off. The first batches of these buses have worked out their resource and 131 of them have been decommissioned. Write-offs were carried out according to the act of the commission with a mileage of 900.0 ... 1400.0 thousand km. However, there is no theoretical justification for the life of the write-off. Therefore, the development of a methodology for writing off rolling stock according to technical condition and economic indicators is relevant.